دور كلا من شدة الألم، القلق، والاكتئاب، والرغبة في الحياة، ونمو ما بعد الصدمة - شويخ,هناء (University of Eloued جامعة الوادي, 2024)
Abstract: This study aims to exploring the role of chronic pain severity, anxiety depression will to live, post-traumatic growth and resilience in functional disability resulting from chronic pain. In order to verify the hypotheses of study, a battery of questionnaires including the demographic questionnaire, The chronic pain severity scale, The general anxiety scale (GAD-7), The patient health questionnaire for depression (PHQ-9), The desire to live scale (WTELS), The posttraumatic growth scale (PTGI), The Connor-Davidson Psychological Resilience Scale (CD-RISC) and The Pain Disability Index (PDI) have been used, The data were collected from a sample (n=211) patients with chronic pain, (130) males and (159) females, there ages ranged from 18-65 years, with a mean of 29.71 (SD = 11.32); The results of the study confirmed that that females are less of the functional disability resulting from chronic pain, and are more anxiety, depression, and the intensity of chronic pain compared to males. The variables of Intensity of chronic pain, depression and resilience are able to predict the degree of functional disability resulting from chronic pain at highly significant levels. تهدف هذه الدراسة إلى استكشاف دور كل من شدة الألم المزمن، والقلق، والاكتئاب، والرغبة في الحياة، ونمو ما بعد الصدمة، والمرونة النفسية في تشكيل خبرة العجز الوظيفي الناتج عن الألم المزمن. وقد اشتملت أدوات الدراسة على: استمارة البيانات الأولية، ومقياس شدة الألم المزمن، ومقياس القلق العام (GAD-7)، واستبيان صحة المريض للاكتئاب (PHQ-9)، ومقياس الرغبة في الحياة (WTELS)، ومقياس نمو ما بعد الصدمة(PTGI) ، ومقياس "كونور ـ دايفيدسون" للمرونة النفسية (CD-RISC)، ومؤشر العجز الناتج عن الألم (PDI). وقد تكونت العينة من (211) مريض بالألم المزمن، (52) ذكر، و(159) أنثى، ويتراوح المدى العمري للعينة ما بين 18 ـ 65 سنة، بمتوسط مقداره 29.71 سنة، وانحراف معياري يقدر بـ ± 11.32 سنة. وجاءت نتائج الدراسة لتؤكد أن الإناث أقل إدراكًا بالعجز الوظيفي الناتج عن الألم المزمن، وأكثر شعورًا بالقلق، والاكتئاب، وشدة الألم المزمن بالمقارنة بالذكور، كما كشفت متغيرات شدة الألم المزمن، والاكتئاب، والمرونة النفسية عن قدرتها التنبؤية بدرجة العجز الوظيفي الناتج عن الألم المزمن بمستويات عالية الدلالة.
والمرونة النفسية في تشكيل خبرة العجز الوظيفي الناتج عن الألم المزمن
Keywords: الألم المزمن; القلق; الاكتئاب; الرغبة في الحياة; نمو ما بعد الصدمة; المرونة النفسية; العجز الوظيفي; Chronic Pain; Anxiety; Depression; Will to live; Post-traumatic growth; Resilience; Functional disability